Communal Space in the Settlement of Cibuntu Sentra Area, Bandung City - Yudi Ariyanto; Karto Wijaya; Heru Wibowo; Amat Rahmat (Universitas Kebangsaan Republik Indonesia [UKRI], 2019)
ABSTRACT : Cibuntu area is a residential area in the city of Bandung that already existed in the colonial era of the Dutch government before independent Indonesia which was partially inhabited by natives and as the settlement of Cibuntu began to be suspended in China and immigrants from the city inhabiting Cibuntu in Bandung became wrong one area with a diverse population. However, in 1937 there was an immigrant from which he founded a small, tofu-producing factory in the Cibuntu area of Bandung. Even though it is a small-scale home industry, the factory is the first and the beginning of the identity of the Cibuntu area as a center for tofu production. But with the time and time of Cibuntu region with limited space the settlement was getting more crowded. This research is intended to provide data and facts that occurred in the Cibuntu area of Bandung. The researcher aims to describe or evaluate what is in the field such as activities, characteristics, relationships, conversations, differences that exist in the field so that this research is not manipulated only to analyze facts / facts that exist in Cibuntu settlementsKeywords : Communal Space, Settlement